Analisis Pengaruh Rasio Keuangan Terhadap Tingkat Pertumbuhan Laba Pada Bank Persero di Indonesia - Sri RUSIYATI (Universitas Bina Sarana Informatika, 2018)
This research was aimed to determine the effect of LDR and ROA on the level of profit growth in state-owned banks in Indonesia listed in Bank Indonesia and Indonesia Stock Exchange. The research period is 5 (five) years from 2010 to 2014. Data collection in this study uses secondary data in the form of data collection from Financial Statement of Bank Persero (BUMN) published in Bank Indonesia and Indonesia Stock Exchange. The sample has been done by using 4 (four) Bank Persero i.e. PT Bank Negara Indonesia (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Tabungan Negara (Persero) and PT Bank Mandiri (Persero) Tbk. The variables in this research are LDR and ROA that influence the profit growth rate as dependent variable, and the analysis has been done by using multiple linear regression analysis. The results of this research showed that partially obtained Loan to Deposit Ratio LDR) has a negative but not significant influence on the level of profit growth and Return On Assets (ROA) has a positive and significant relationship to profit growth. Factors affecting the growth rate of earnings can be explained by the independent variables of 86.90% caused by LDR and ROA, while the remaining 13.1% is caused by other factors not included in this estimate such as exchange rate, interest rate, monetary policy, inflation rate etc.